2014
DOI: 10.1080/00207160.2014.957688
|View full text |Cite
|
Sign up to set email alerts
|

Haar wavelet-based numerical investigation of coupled viscous Burgers' equation

Abstract: In this work, numerical solutions of the nonlinear coupled Burgers' equation with appropriate initial and boundary conditions in one space dimension are considered. A numerical method is proposed using the properties of uniform Haar wavelets together with a collocation method and based on semi-discretization along the space direction for solving a coupled viscous Burgers' equation. The semi-discretization scheme forms a system of nonlinear ordinary differential equations which is solved by the fourth-order Run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Lastly we consider the coupled Burgers' equation (1.1), (1.2) for α = β = 1 and η = ξ = −2 so that equations (1.1), (1.2) take the following form: Table 4. The obtained results by the present method are in good agreement with Haar wavelet method [29] and are better than Finite element method [23]. The physical behavior of numerical solutions for α = β = 1 and η = ξ = −2 between t = 0 and t = 2 and for α = 3, β = 2 and η = 1, ξ = −2 between t = 0 and t = 1.5 are depicted with contour forms in Fig.…”
Section: Problemsupporting
confidence: 73%
See 2 more Smart Citations
“…Lastly we consider the coupled Burgers' equation (1.1), (1.2) for α = β = 1 and η = ξ = −2 so that equations (1.1), (1.2) take the following form: Table 4. The obtained results by the present method are in good agreement with Haar wavelet method [29] and are better than Finite element method [23]. The physical behavior of numerical solutions for α = β = 1 and η = ξ = −2 between t = 0 and t = 2 and for α = 3, β = 2 and η = 1, ξ = −2 between t = 0 and t = 1.5 are depicted with contour forms in Fig.…”
Section: Problemsupporting
confidence: 73%
“…. In the studies [22,29], coupled Burgers' equations are solved by Haar wavelet method. Rashid et al have solved the coupled viscous Burgers' equation by Chebyshev-Legendre Pseudo-Spectral method in [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the problem are reported in Table XIII. In Table XIII, compared L ∞ and RMS errors of LRBF-DQM and GRBF-DQM for a0=0.05, A=a02(4αβ12α1) and it is concluded that LRBF-DQM algorithm is better than GRBF-DQM and other schemes proposed in Mittal et al (2015) and Rashid and Ismail (2009).…”
Section: Numerical Experiments and Discussionmentioning
confidence: 97%
“…After this achievement researchers have been using Haar wavelets to obtain numerical solutions of differential equations because of their simplicity and computational features. Recently, many authors have used Haar wavelet method for solving ordinary and partial differential equations [20][21][22][23][24][25][26][27][28][29][30][31]. Especially high order pdes like KdV and fractional coupled KdV equations are considered in [32,33].…”
Section: Haar Waveletsmentioning
confidence: 99%